Marketing Evaluation as a Profession and Discipline - E. Jane Davidson (Journal of MultiDisciplinary Evaluation, 2005)
It can be a bit like pushing sand uphill with a pointy stick, as they say here in New Zealand. One of the great challenges in developing evaluation as a discipline is getting it recognised as being distinct from the various other disciplines to which it applies. In this piece, I offer a few reflections on the challenges with this, recount a story where a group of practitioners from outside the discipline actually sat up and took notice, and propose some possible solutions for moving us forward.